Does the Posterior Bending Osteotomy in Bilateral Sagittal Split Osteotomy Affect the Condyle Position in Asymmetric Patients? - Pergel, Taha; Bilge, Suheyb; Demirbaş, Ahmet Emin; Kütük, Nükhet (My University, 2023)
To measure and compare changes in postoperative condylar position following bilateral sagittal split osteotomy in patients with asymmetry treated using a posterior bending osteotomy (PBO) and conventional methods (shaving of premature contacts).

Participants were randomized to either the PBO or conventional group. The inclusion criteria were the need for bilateral sagittal split osteotomy or bimaxillary asymmetric surgery (menton deviation >4 mm). The primary outcome variable was changes in the condylar position in the axial, coronal, and sagittal planes 6 months after surgery, whereas the secondary outcome variable was changes in temporomandibular joint symptoms. Covariates included surgery type, deformity type, age, and sex. Categorical and numerical variables were analyzed using Fisher exact χ test and 2-way analysis of covariance.

The study sample comprised 42 patients with a mean age of 23.3 years; 57.5% were women. The alteration in the coronal condyle angle was 0.8⁰ ± 0.86⁰ in the PBO and 2.72⁰ ± 0.81⁰ in the conventional group. The differences in the condylar position in the coronal plane were not statistically significant (P = .129). The alteration in the axial condyle angle was 2.31⁰ ± 1.74⁰ in the PBO group and 5.65⁰ ± 1.65⁰ in the conventional group. The alteration in the sagittal plane was 0.44⁰ ± 1.52⁰ in PBO and 0.47⁰ ± 1.44⁰ in the conventional group. Alterations in axial (P = .194) and sagittal (P = .976) condylar positions were insignificant. In the conventional group, statistically significant differences were found in the axial (P = .002) and coronal (P = .002) planes, and the condyle turned inward in both planes. There were no statistically significant differences between the groups or within the groups in the sagittal plane (P > 0,5). In PBO and conventional groups, joint noise examination revealed positive results in 11 and 6 patients preoperatively and 1 and 2 patients postoperatively, respectively. A statistically significant decrease in joint noise was detected in the PBO group (P = 0,04). The maximum mouth opening without pain was 5.95 ± 1.47 in the PBO group and 7.91 ± 1.39 in the conventional group, respectively. The alteration was not statistically significant between the groups but was significant within the groups (P < .001).

PBO effectively prevents premature contact between mandibular segments in facial asymmetry.